Pengembangan Sistem Pelaporan Online untuk Kasus Kekerasan Seksual: Pendekatan Extreme Programming di Bengkalis - Nadiatul Husna, Mella; Profesio Putra, Fajri; Rahmi, Elvi (Universitas Multi Data Palembang, 2024)
Sexual violence is a serious issue affecting women and children across various regions of Indonesia, including Bengkalis Island. Victims of sexual violence require optimal support in handling and prosecuting perpetrators. Currently, reporting requires direct visits to the Women and Children Protection Unit in Bengkalis District, which is inefficient. This study aims to create an online reporting and consultation application to enhance reporting efficiency. Extreme Programming is employed as the research method. Results indicate positive community feedback, demonstrating satisfaction with the application's ability to facilitate online reporting and consultations with the Women and Children Protection Unit in Bengkalis District, aligning with anticipated outcomes.